Intramedullary Subependymoma of Lower Thoracic Cord - Hafiza Hifza Bashir; Hafiza Fatima Aziz; Muhammad Shahzad Shamim (Journal of the Pakistan Medical Association, 2023)
Spinal subependymoma (SSE) is a rare intramedullary, benign tumour. Surgical excision is the preferred approach. However, the interwoven pattern of neural tissue within the tumour dictates the extent of resection. Where gross total resection is linked with possible neurological deficits, subtotal resection or close observation may support better functional outcomes. The evidence for the management of SSE is based mostly on case reports. Herein, we review the existing literature regarding treatment options and clinical outcomes of spinal subependymoma.